Human papillomavirus type 8 interferes with a novel C/EBPβ-mediated mechanism of keratinocyte CCL20 chemokine expression and Langerhans cell migration. - Tanya Sperling; Monika Ołdak; Barbara Walch-Rückheim; Claudia Wickenhauser; John Doorbar; Herbert Pfister; Magdalena Malejczyk; Sławomir Majewski; Andrew C Keates; Sigrun Smola (PLoS Pathogens)
Infection with genus beta human papillomaviruses (HPV) is implicated in the development of non-melanoma skin cancer. This was first evidenced for HPV5 and 8 in patients with epidermodysplasia verruciformis (EV), a genetic skin disease. So far, it has been unknown how these viruses overcome cutaneous immune control allowing their persistence in lesional epidermis of these patients. Here we demonstrate that Langerhans cells, essential for skin immunosurveillance, are strongly reduced in HPV8-positive lesional epidermis from EV patients. Interestingly, the same lesions were largely devoid of the important Langerhans cells chemoattractant protein CCL20. Applying bioinformatic tools, chromatin immunoprecipitation assays and functional studies we identified the differentiation-associated transcription factor CCAAT/enhancer binding protein β (C/EBPβ) as a critical regulator of CCL20 gene expression in normal human keratinocytes. The physiological relevance of this finding is supported by our in vivo studies showing that the expression patterns of CCL20 and nuclear C/EBPβ converge spatially in the most differentiated layers of human epidermis. Our analyses further identified C/EBPβ as a novel target of the HPV8 E7 oncoprotein, which co-localizes with C/EBPβ in the nucleus, co-precipitates with it and interferes with its binding to the CCL20 promoter in vivo. As a consequence, the HPV8 E7 but not E6 oncoprotein suppressed C/EBPβ-inducible and constitutive CCL20 gene expression as well as Langerhans cell migration. In conclusion, our study unraveled a novel molecular mechanism central to cutaneous host defense. Interference of the HPV8 E7 oncoprotein with this regulatory pathway allows the virus to disrupt the immune barrier, a major prerequisite for its epithelial persistence and procarcinogenic activity.